2018
DOI: 10.26719/emhj.18.009
|View full text |Cite
|
Sign up to set email alerts
|

Successful implementation of general health policies in the Islamic Republic of Iran: barriers and mechanisms

Abstract: Background: The general health policies for the Islamic Republic of Iran were approved in April 2014. Aims: This study examined the barriers currently faced by general health policies and the mechanisms required for the successful implementation of these polices. Methods: This qualitative study was conducted as a two-phase project based on standard CAN-IMPLEMENT guidelines. A set of qualitative methods, including face-to-face in-depth interviews, focus groups, and in-person consensus meetings, were used to cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Accordingly, several studies have concluded that a comprehensive national action plan for the implementation of GHP is necessary. [ 43 44 45 ]…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, several studies have concluded that a comprehensive national action plan for the implementation of GHP is necessary. [ 43 44 45 ]…”
Section: Discussionmentioning
confidence: 99%
“…10 One of the major aims of the HTP is to increase the financial risk protection among Iranian population, particularly the poor and vulnerable, which was endorsed by national general health policies by 2025. 11 The HTP extended basic health insurance coverage to approximately 10 million people, increasing those covered from 83.2% of the population to 93.2%. 12 According to SDG1, countries are committed to end poverty in all forms and dimensions by 2030 by implementing necessary measures and interventions.…”
Section: Highlightsmentioning
confidence: 99%
“…As in many other countries, the recent health reforms in Iran are guided by the concept of UHC 10 . One of the major aims of the HTP is to increase the financial risk protection among Iranian population, particularly the poor and vulnerable, which was endorsed by national general health policies by 2025 11 . The HTP extended basic health insurance coverage to approximately 10 million people, increasing those covered from 83.2% of the population to 93.2% 12…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, in Iran, community-based geriatric services, as well as the policy of providing integrated services, have quantitative and qualitative defects especially in implementation process [ 24 ]. The most important obstacles to the implementation of general health policies in Iran were the lack of formulated strategies, poor management, lack of a comprehensive national action plan, minimal information infrastructure, and insufficient funding [ 25 ]. Consequently, due to the difference in health and support system policies especially for older adults in Iran compared to other countries, the levels of functional status or ability to perform basic and instrumental activities of daily living can be different in older adults, therefore, the results in other countries may not be generalizable to Iran.…”
Section: Introductionmentioning
confidence: 99%